Analysis of droplet size distribution and selection of spray parameters based on the fractal theory. (15th October 2022) - Fan, Siyu; Chen, Shiqiang; Wu, Zhirong; Wu, Shixian; Chen, Yongping; Liu, Dong; Yao, Yuhong; Huang, Junxin
Abstract: Using multiple parameters to represent the droplet size distribution (DSD) always leads to various outcomes that make it hard to decide. The research combined theoretical derivation with experiments to study the random fractal of the DSD. The function of the DSD was deduced, and the fractal dimension (FD) was used as an independent parameter to characterize the DSD. The DSD was measured by the Malvern measuring apparatus under different spray pressure. The results showed that the FD of the five nozzles measured experimentally is between 1.5 and 3. The independent parameter FD has more advantages than multi-parameters (the Sauter mean diameter and the size distribution span). In the air cleaning technology by spray, the FD was used as an evaluation parameter. The optimal distance from the nozzle to the wetting fine wire plate was determined to be 75–85 cm, and the total dust efficiency of the wetting fine wire plate air cleaning device can reach 98.98%. Highlights: The size distribution of droplets is fractal. The fractal dimension of droplets is mainly concentrated in the range of 1.5–3. A method for evaluating the droplets distribution by fractal dimension is proposed. The optimal installation distance of nozzles in the dust removal device is 75–85 cm.